As novas configurações do espaço agrário no Rio Grande do Sul / Brasil: da pecuária tradicional ao complexo agroindustrial da soja - Vinicius Silva Moreira; Rosa Maria Vieira Medeiros (Confins)
New agrarian area settings in Rio Grande do Sul / Brasil: to the traditional livestock to the soybean agroindustrial complex The state of Rio Grande do Sul/Brazil has undergone significant transformations in its agricultural area in the last decades. The Northwest South rio-grandense was the main stage of this transformation, as it was the primary site of the Seven Jesuit Missions (Reduções Jesuíticas dos Sete Povos Missioneiros), with an economy based on extensive cattle raising, which later was consolidated with the pastoral landowners. In the same area, in the decade since the year 1970, there is a partial fragmentation of the breeding of cattle and restructuring occurs through the leasehold or sale of the properties in favor of soy agribusiness. To examine the evolution of spatial restructuring of this state during the period between 1975 to 2006, analyzing the transformations in production and land responsible for the formation of a new spatial configuration, are the objectives of this research. The methodology is analytical-descriptive, based on fieldwork, through observations and interviews with farmers and landowners, and other qualified informants.